2014
DOI: 10.1016/j.neuroimage.2013.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Measuring temporal, spectral and spatial changes in electrophysiological brain network connectivity

Abstract: ABSTRACT:The topic of functional connectivity in neuroimaging is expanding rapidly and many studies now focus on coupling between spatially separate brain regions. These studies show that a relatively small number of large scale networks exist within the brain, and that healthy function of these networks is disrupted in many clinical populations. To date, the vast majority of studies probing connectivity employ techniques that compute time averaged correlation over several minutes, and between specific pre-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 46 publications
3
113
0
Order By: Relevance
“…Second, when estimating functional connectivity itself, most correlative or coherence based measures are highly sensitive to the number of degrees of freedom in the timecourses used to generate them. 2) In addition to the technical limitation, the well characterised dynamic nature of functional connectivity, which changes over seconds, and even milliseconds Brookes et al, 2014;Chang and Glover, 2011;Hutchison et al, 2013;G C O'Neill et al, 2015 b;O'Neill et al, 2016) must be considered, since there is a question regarding how well a short time window can capture the canonical MEG networks, if those networks are constantly changing across multiple time-scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, when estimating functional connectivity itself, most correlative or coherence based measures are highly sensitive to the number of degrees of freedom in the timecourses used to generate them. 2) In addition to the technical limitation, the well characterised dynamic nature of functional connectivity, which changes over seconds, and even milliseconds Brookes et al, 2014;Chang and Glover, 2011;Hutchison et al, 2013;G C O'Neill et al, 2015 b;O'Neill et al, 2016) must be considered, since there is a question regarding how well a short time window can capture the canonical MEG networks, if those networks are constantly changing across multiple time-scales.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the excellent temporal precision afforded by MEG allows estimation of dynamic changes in network structure Brookes et al, 2014;O'Neill et al, 2015a). The importance of characterising electrophysiological connectivity is growing, with numerous demonstrations that connections are perturbed in pathologies Friston, 1998;Guggisberg et al, 2008;Kessler et al, 2014;Palaniyappan and Liddle, 2012;Schnitzler and Gross, 2005;Stufflebeam et al, 2011;Tewarie et al, 2014;van Dellen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most current connectivity studies assume stationarity to avoid the high complexity involved in modeling the dynamic signal information, which limits the ability to process connectomes with more than 10–20 regions (Smith, 2012). Nevertheless, the extension of our framework, using for example sliding-window correlations, to examine the dynamic complexity of the underlying signals is of particular interest (Brookes et al, 2014). Here, we examine brain connectivity based on the precision matrix, which is the inverse of the covariance matrix and it reflects partial correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Measures based on temporal correlations between the amplitude envelopes of neural oscillations have been increasingly used to investigate functional connectivity. [56][57][58][59][60][61][62][63] It has been suggested that such connectivity measures are conceptually more similar to those obtained with fMRI than coherence-based methods. 56 It has indeed been shown that amplitude envelope correlations in various frequency bands (including the gamma band) adequately reflect interactions within and between resting-state networks depicted by fMRI.…”
Section: Eeg Recording and Connectivity Analysesmentioning
confidence: 99%